2020
DOI: 10.1002/csc2.20040
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and genetic assessment of terminal drought tolerance in two‐row spring barley

Abstract: Barley (Hordeum vulgare L.) ranks fourth in global cereal grain production and is an important crop for animal feed, malting, and human consumption. Identification of two-row barley germplasm with drought tolerance can increase genetic diversity and facilitate future barley breeding efforts. The present study evaluated 480 two-row spring barley accessions from the USDA National Small Grains Collection across two years of irrigated and terminal drought trials for grain yield, test weight, protein content, thous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…1); which indicates the importance of the locus to govern multiple traits. Gordon et al (2020) also detected the association of multiple traits such as heading date, plant height, and kernel length on chromosome 2H at 27.2-29.8 Mbp in field drought stress experiments. Such effects may be due to the tight linkage of genes or the pleiotropic effect of a single gene (Hall et al 2006).…”
Section: Discussionmentioning
confidence: 86%
“…1); which indicates the importance of the locus to govern multiple traits. Gordon et al (2020) also detected the association of multiple traits such as heading date, plant height, and kernel length on chromosome 2H at 27.2-29.8 Mbp in field drought stress experiments. Such effects may be due to the tight linkage of genes or the pleiotropic effect of a single gene (Hall et al 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Gordon et al. (2020) evaluated a large number of barley genotypes and found clear genotype variation with specific selections maintaining lower protein under terminal drought. Additionally, N applications were controlled at a single rate in the study and lower N rates could be further researched as they have been shown to positively reduce grain protein; however, these N reductions can also negatively affect yield.…”
Section: Resultsmentioning
confidence: 99%
“…Gordon et al. (2020) identified QTLs near the QGF‐7H locus as being associated with measures of barley seed size under terminal drought conditions. An early start to the grain fill period could be particularly beneficial for starch accumulation in environments such as Havre that depend on finite stores of soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…The Pauli study also mapped plump and test weight near both loci, as well as multiple direct measures of malt quality such as betaglucan content, free amino nitrogen, and malt extract near QGFhd-2H. Gordon et al (2020) identified QTLs near the QGF-7H locus as being associated with measures of barley seed size under terminal drought conditions. An early start to the grain fill period could be particularly beneficial for starch accumulation in environments such as Havre that depend on finite stores of soil moisture.…”
Section: Earlier Headingmentioning
confidence: 99%
See 1 more Smart Citation